(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
The uniqueness of interpersonal communication in Aspuri Sultra-Yogyakarta lies in their communication patterns, which are still influenced by the dialect of each ethnic group, even though the female students study and migrate to Yogyakarta, they still use the Southeast Sulawesi accent in their daily communication. This topic is interesting to discuss considering that no one has addressed interpersonal communication in Aspuri Sultra-Yogyakarta. Therefore, the main issues discussed are the concept of interpersonal communication, how the female dormitory residents maintain solidarity through interpersonal communication, and what factors support and hinder interpersonal communication in maintaining solidarity in Aspuri Sultra-Yogyakarta. In this study, the communication method used is the persuasive method. Data analysis is conducted qualitatively with stages of data reduction, data presentation, and conclusion drawing. Research results show that in an effort to maintain solidarity in Aspuri Sultra-Yogyakarta, residents adopt the concept of openness regarding feelings and thoughts to prevent misunderstandings. Furthermore, the quality time agenda held every month is one way to strengthen brotherly relationships. The presence of dialogues and familiarity serves as supporting factors in interpersonal communication. However, the differences in dialects used have become an element that leads to misunderstandings in interpreting words, and a lack of empathy and supportive attitudes are also significant obstacles to effective communication